Trends in Research on Strategic Communication, Strategic Integrated Communication, Personal Branding and Brand Advocacy in the Context of Higher Education. - Jacobus M. De Villiers; Anette Degenaar; Lynnette Fourie (Communicare)
Higher education institutions in South Africa find themselves in situations of strategic complexity due to contextual changes in the higher education landscape. One of these challenges is the complexity of stakeholders within the higher education context, specifically students and alumni. In this regard, students function as internal stakeholders, and once they graduate, they become external stakeholders. Furthermore, due to their connection with a higher education institution, both students and alumni, through their personal brands, can contribute to or diminish strategic communication endeavours by higher education brands. Thus, an integrated communication approach is needed to strategically align student and alumni personal brands with higher education institution brands. Through a systematic literature review, this study explored the integration of relevant concepts to the problem at hand: strategic communication, strategic integrated communication, brand advocacy and personal branding. The conducted review found that these theoretical concepts had limited theoretical overlap with concepts covered in academic articles found on selected academic databases. The absence of interrelatedness between the theoretical foundations and empirical evidence of these concepts highlights the gap in research on the complexity of stakeholders in higher education from a strategic communication perspective. This article adds value to the perspectives on stakeholders in higher education institutions.